The Evolution of Local Labor Markets after Recessions - Brad J. Hershbein; Bryan Stuart (Institute of Labor Economics (IZA), 2023)
This paper studies how U.S. local labor markets respond to employment losses that occur during recessions. Following recessions from 1973 through 2009, we find that areas that lose more jobs during the recession experience persistent relative declines in employment and population. Most importantly, these local labor markets also experience persistent decreases in the employment-population ratio, earnings per capita, and earnings per worker. Our results imply that limited population responses result in longer-lasting consequences for local labor markets than previously thought, and that recessions are followed by persistent reallocation of employment across space.
Keywords: J21; J61; R23; 330; local labor markets; recessions; employment rates; migration